Active Materials for Organic Electrochemical Transistors. Issue 44 (18th July 2018) - Zeglio, Erica; Inganäs, Olle
Abstract: The organic electrochemical transistor (OECT) is a device capable of simultaneously controlling the flow of electronic and ionic currents. This unique feature renders the OECT the perfect technology to interface man‐made electronics, where signals are conveyed by electrons, with the world of the living, where information exchange relies on chemical signals. The function of the OECT is controlled by the properties of its core component, an organic conductor. Its chemical structure and interactions with electrolyte molecules at the nanoscale play a key role in regulating OECT operation and performance. Herein, the latest research progress in the design of active materials for OECTs is reviewed. Particular focus is given on the conducting polymers whose properties lead to advances in understanding the OECT working mechanism and improving the interface with biological systems for bioelectronics. The methods and device models that are developed to elucidate key relations between the structure of conducting polymer films and OECT function are discussed. Finally, the requirements of OECT design for in vivo applications are briefly outlined. The outcomes represent an important step toward the integration of organic electronic components with biological systems to record and modulate their functions. Abstract : The organic electrochemical transistor (OECT) is gaining increased attention as a promising device for bioelectronics. Its function hinges on the mixed ionic and electronic conductivity of conducting polymers. The structure–property relationships governing OECT operation and performance are presented. An overview is given on the current strategies and future directions toward effective interfaces of OECTs with biological systems.